WHY WRITE? (The Pretoria Student Law Review, 2021)
How to respond to the question why write? And the question, I hasten to add, why read? And maybe the most pertinent one, why think? For me these questions are members of the same family, and like most if not all families live together in precarious and sometimes troubling ways. Writing, without reading and thinking, could end up in one of those over-simplified presentations of family life, falsely portraying the home as a one-dimensional, unreflective, necessarily safe and uncritical entity. However, as a diligent student I will keep to my task at hand and attempt a contemplation of the first question.
Keywords: why write; why read; why think